Anti-cancer and mechanism of action of phytic acid: therapeutic effects of rice bran phytic acid on colon cancer in vitro and in vivo - Shafie, Nurul Husna; Mohd Esa, Norhaizan (LAP Lambert Academic Publishing, 2014)
Colon cancer is a major neoplastic disease affecting men and women worldwide. Rice bran is one of the richest sources of dietary fiber and contains phytonutrients, including phytic acid, known to possess various medicinal properties. Phytic acid, or inositol hexaphosphate (IP6) has been suggested to play a significant role in the inhibition of colon cancer. Thus, our attention was drawn to the possibility to utilize the local source of phytic acid in identifying non-toxic anti-cancer agents that can potentially lead to the development of better treatments for colon cancer.